2022
DOI: 10.15252/embr.202255044
|View full text |Cite
|
Sign up to set email alerts
|

SCF FBXW7 regulates G2‐M progression through control of CCNL1 ubiquitination

Abstract: FBXW7, which encodes a substrate-specific receptor of an SCF E3 ligase complex, is a frequently mutated human tumor suppressor gene known to regulate the post-translational stability of various proteins involved in cellular proliferation. Here, using genomewide CRISPR screens, we report a novel synthetic lethal genetic interaction between FBXW7 and CCNL1 and describe CCNL1 as a new substrate of the SCF-FBXW7 E3 ligase. Further analysis showed that the CCNL1-CDK11 complex is critical at the G2-M phase of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…A recent study identified OTS964 as a potent and specific inhibitor of CDK11 that displayed a toxic effect on cancer cells (Lin et al , 2019). Another study demonstrated that cancer cell lines with mutations in the tumor‐suppressor gene FBXW7 require CDK11 activity for survival, further emphasizing its importance in cancer (O'Brien et al , 2022). Developing effective and selective inhibitors for CDK11 is dependent on understanding the active CDK11 complex, as CDK inhibitors are typically developed against purified CDK‐cyclin complexes (Wells et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified OTS964 as a potent and specific inhibitor of CDK11 that displayed a toxic effect on cancer cells (Lin et al , 2019). Another study demonstrated that cancer cell lines with mutations in the tumor‐suppressor gene FBXW7 require CDK11 activity for survival, further emphasizing its importance in cancer (O'Brien et al , 2022). Developing effective and selective inhibitors for CDK11 is dependent on understanding the active CDK11 complex, as CDK inhibitors are typically developed against purified CDK‐cyclin complexes (Wells et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes are known negative regulators of Wnt pathway, e.g., APC and AXIN1 , so that their knockout provides downstream activation of Wnt/β-catenin signaling. These genes were independently observed in a genome-wide in vitro screen performed by the Angers group ( 20 ) aiming to find resistance genes against another PORCN inhibitor. One unexpected hit from both screens was FBXW7 , a known tumor suppressor but one that is not obviously involved in regulating Wnt signaling ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, there might be other substrates not examined in our study that also contributed to cell cycle progression after FBXW7 mutation. For example, another cell cycle regulator, Cyclin L1, was recently identified as a novel substrate of FBXW7 and accumulated in FBXW7-inactivated cells ( 20 ). Elevated levels of Cyclin L1 might also help to maintain the active cell cycle during Wnt inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there might be other substrates not examined in our study that also contributed to cell cycle progression after FBXW7 mutation. For example, another cell cycle regulator Cyclin L1 was recently identified as a novel substrate of FBXW7 and accumulated in FBXW7-inactivated cells 19 . Elevated levels of Cyclin L1 might also help to maintain the active cell cycle during Wnt inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes are known negative regulators of Wnt pathway, e.g., APC and AXIN1, so that their knockout provides downstream activation of Wnt/β-catenin signaling. These genes were independently observed in a genome-wide in vitro screen performed by the Angers group aiming to find resistance genes against another PORCN inhibitor 19 . One unexpected hit from both screens was FBXW7, a known tumor suppressor but one that is not obviously involved in regulating Wnt signaling 20 .…”
Section: Recurrent Fbxw7 Mutations In Rnf43-mutant/rspo-fusion Cancersmentioning
confidence: 99%